The Influence of Group Guidance-Based Cooperative Learning Methods on Collaboration and Social Interaction Skills of Students at SMPN 2 Bantan - Tina Murdiati; Nurmalina; Imam Hanafi (ASIAN: Indonesian Journal of Learning Development and Innovation, 2024)
This study aims to analyze the effect of the Cooperative Learning method based on group guidance on the collaboration and social interaction skills of students at SMPN 2 Bantan. The research was conducted over a period of two weeks, with a series of activities including pretest, intervention, and posttest. Data were taken from 10 students who were the subjects of the study. During the study, a pretest was conducted at the beginning to determine the initial conditions of the students, followed by four intervention meetings using the Cooperative Learning method based on group guidance, and a posttest at the end of the period to measure the changes that occurred. Based on the results of the study, it can be concluded that the Cooperative Learning method based on group guidance has a significant effect on improving the collaboration and social interaction skills of students at SMPN 2 Bantan. The significant increase in these two variables indicates that the Cooperative Learning method based on group guidance is not only effective in improving collaboration skills, but is also able to improve students' social interactions. This is important because collaboration and social interaction skills are vital components in the learning process and character development of students.